Life Satisfaction Level: A Study of Traditional Fishermen in Paluh Sibaji Village, Deli Serdang District, Indonesia - Umi Salmah; Sri Malem Indirawati; Annisa Rizka Lestari; Najwa Nandita Dwinda; Dinda Fachrani Akri (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Indonesia ranks 80th in the world’s happiness index, lagging behind neighboring countries such as Singapore (30th), Malaysia (59th), and Thailand (58th). The happiness index consists of three dimensions: life satisfaction (education, work, and home facilities), feelings (happiness, anxiety, and depression), and meaningfulness of life (independence, environmental mastery, and self-acceptance). In 2021, North Maluku was the happiest province while North Sumatra had the lowest happiness index, nationally ranking seventh lowest and being one of the provinces with poor incomes, education, and housing facilities experienced by fishermen in Indonesia. This study aims to analyze the Life Satisfaction Level among fishermen. This was a descriptive cross-sectional study with 107 samples taken based on the Slovin formula from the population of 700 people. The data was obtained by using a questionnaire that had been tested for the validity and reliability. A univariate data analysis was performed by using SPSS version 25. The results showed that 47.66% respondents were >45 years old, 43.93% completed junior high school, 7.67% had 5-10 years of work experience, and 57.94% smoked. While 52.34% perceived their quality of life as not good, 85.98% felt not secure about old age, 77.57% felt their jobs did not meet financial needs, 82.24% reported their finance was not good enough, 60.75% felt their health quality was not good, and 74.77% found their living conditions were inadequate. Moreover, 64.49% considered that their sleep quality was not good, 77.57% had bad social relationships, and 64.49% struggled to manage negative emotions. Only 47.67% of the fishermen considered that their quality of life was good. Most of these traditional fishermen had low levels of life satisfaction. Therefore, improving welfare through expansion of economic opportunities, access to health services, and community-based social support is needed to enhance the quality of life and resilience of the fishermen. Keywords: Fishermen, Life, Satisfaction, Traditional , Worker.